(untitled) (Международный научный журнал «Инженер», 2026)
This article studies the propagation of one-dimensional spherical shock waves in a homogeneous medium, represented by soil or ground, modeled as a continuous elastic-plastic medium. The research assumes that the loading shock waves in the elastic-plastic medium filling the surrounding space propagate at a constant velocity. Furthermore, the effective use of directional blasting technology in construction, mining-geological industries, and other technical fields requires determining the relevant mechanical parameters of continuous elastic-plastic media subjected to shock loads. Within the theory of small elastic-plastic deformations, the relationship between the components of the stress and strain tensors in a spherical coordinate system is taken into account.